Medieval Hindu law historical evolution and enlightened rebellion - Mathur, Ashutosh Dayal (New Delhi ; Oxford : Oxford University Press, 2007)
Based on a detailed study of 7 leading Sanskrit texts written during that period as well as significant commentaries on the smrtis and dharma sutras, the book focuses on the changes which took place at the time, and their subsequent reflection in the texts. It explores how and why Hindu law emerged from the shadows of dharma and established itself independently as vyavahara.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Hindu law -- History; Hindu civilization; India -- Social life and customs